2015
DOI: 10.4049/jimmunol.1402242
|View full text |Cite
|
Sign up to set email alerts
|

Rpl22 Loss Impairs the Development of B Lymphocytes by Activating a p53-Dependent Checkpoint

Abstract: While ribosomal proteins facilitate the ribosome’s core function of translation, emerging evidence suggests that some ribosomal proteins are also capable of performing tissue restricted functions either from within specialized ribosomes or from outside of the ribosome. In particular, we have previously demonstrated that germline ablation of the gene encoding ribosomal protein Rpl22 causes a selective and p53 dependent arrest of αβ T cell progenitors at the β-selection checkpoint. We have now identified a cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
(81 reference statements)
1
24
0
Order By: Relevance
“…Thus, it may be the abrupt transition from quiescence to rapid proliferation that sensitizes Rpl22-deficient αβ lineage progenitors to arrest. Consistent with this notion, we observe a similar arrest at the equivalent stage of B lymphoid development, where pre-B cell receptor signals induce a comparably abrupt transition to rapid proliferation (53). Nevertheless, we have not yet been able to test the causal relationship between proliferation and arrest, which could entail blunting the capacity of Rpl22-deficient αβ lineage progenitors to proliferate.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, it may be the abrupt transition from quiescence to rapid proliferation that sensitizes Rpl22-deficient αβ lineage progenitors to arrest. Consistent with this notion, we observe a similar arrest at the equivalent stage of B lymphoid development, where pre-B cell receptor signals induce a comparably abrupt transition to rapid proliferation (53). Nevertheless, we have not yet been able to test the causal relationship between proliferation and arrest, which could entail blunting the capacity of Rpl22-deficient αβ lineage progenitors to proliferate.…”
Section: Discussionsupporting
confidence: 82%
“…Despite the ubiquitous expression of Rpl22, its germline ablation does not result in embryonic lethality or gross abnormalities in mice, but does result in profound reductions in selected peripheral lymphocyte populations 98 . Indeed, Rpl22-deficient mice have striking decreases in splenic CD4 and CD8 T cells, and somewhat more modest reductions in splenic B2 cells and B1 B cells present in the peritoneal cavity 98,134 . Surprisingly, Rpl22-deficient peripheral B cells appear fully functional, as they are able to proliferate in response to mitogenic stimulation, upregulate activation markers, and undergo class switch recombination.…”
Section: Bodymentioning
confidence: 99%
“…Surprisingly, Rpl22-deficient peripheral B cells appear fully functional, as they are able to proliferate in response to mitogenic stimulation, upregulate activation markers, and undergo class switch recombination. Initial studies reported that Rpl22-deficient T cells were unable to proliferate in response to TCR stimulation 98 ; however, this is likely to be due to the extensive homeostatic proliferation that occurs in Rpl22-deficient mice, which are lymphopenic because of limited thymic output 134 . While these studies do not rule out a role for Rpl22 in peripheral immune responses, they suggest that the predominant role of Rpl22 is likely to be in supporting normal lymphoid development.…”
Section: Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Rpl22 is dispensable for ribosome biogenesis and global, cap-dependent translation; however, Rpl22 does play a critical, lineage-restricted role in supporting hematopoiesis (4, 5). Indeed, despite the ubiquitous expression of Rpl22, Rpl22-null mice are viable and fertile, with the only obvious defect being an exquisitely specific p53-dependent block in certain lymphoid subsets, including αβ lineage T cells (5, 6). The tissue-restricted nature of the developmental abnormalities caused by Rpl22-deficiency, clearly distinguish Rpl22 from other RPs, whose loss usually results in early lethality (3, 7).…”
Section: Introductionmentioning
confidence: 99%